(untitled) (Bioresearch Communications, 2023)
Emerging antibiotic resistance of Gram-positive bacteria leading to strikethrough infections are one of the major threats to global public health. This research aimed to determine different circulating Gram-positive bacterial species as well as their antibiotic resistance pattern along with their phylogenetic analysis. Fifty (50) Gram-positive isolates from different bacterial species were isolated from eight different hospital cafeteria fast foods of Dhaka, Bangladesh of which 58% of the isolates were from sandwiches and 42% of the isolates were from burger samples. The isolates were divided into six different groups based on different biochemical tests belonging to Bacillus spp. followed by Planococcus spp., Micrococus spp., Streptococcus spp., Clostridium spp. and Staphylococcus spp. Distribution of isolates varied greatly keeping the highest number of isolates from Bacillus spp. and lowest in Staphylococcus spp. BLAST search and phylogenetic analysis revealed that all sequenced isolates were Gram-positive bacteria under firmicutes and shared their identity with Chryseomicrobium spp., Sporosarcina psychrophila, Bacillus licheniformis. About 6% of the isolates were strong biofilm former whereas 4%, 24% and 66% of the isolates were moderate biofilm formers, weak biofilm formers and non-biofilm formers respectively. About 6% of the isolates showed β-hemolytic properties. About 72% of the isolates were multi-drug resistant. Among the antibiotics, ampicillin and penicillin showed the highest level of resistance followed by cephalexin, nitrofurantoin, meropenem and no resistance to imipenem. A higher proportion of multi-drug resistant (MDR) Gram-positive isolates were revealed from the hospital cafeteria fast foods demonstrating the risky situation regarding hospital associated infections caused by Gram-positive bacteria. Bioresearch Commu. 10(1): 1361-1370, 2024 (January)